Analysis of the Success of Online Learning During a Pandemic: A Survey Study in Madrasah Tsanawiyah (MTs) Pekanbaru City - Sohiron, Sohiron; Fitriyadi, Muhammad; Ismail, Ismail; Vebrianto, Rian; Thahir, Musa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Analysis of the Success of Online Learning during a Pandemic: A Survey Study in Madrasah Tsanawiyah (MTs) Pekanbaru City. Objectives: This article is motivated by the obstacles faced during online learning, ranging from technical problems to the learning process, such as networks, quota costs that are quite expensive, operating Google Meet applications, Google Classroom, and other E-learning applications with the correct procedures, to the use of cameras and microphones that are sometimes not properly working. Understanding the obstacles that occur in the field regarding online learning activities, and reviewing the success of online learning is necessary. Therefore, this article aims to find out the extent of the success rate of online learning that occurs in Madrasah Tsanawiyah Pekanbaru City. Methods: The research is survey research with a quantitative approach that examines the success of online learning during the COVID-19 pandemic in Pekanbaru city. The research was carried out in MTs in Pekanbaru City consisting of 6 madrasahs, namely 3 Public MTs and 3 Private MTs. The data collection was done using a questionnaire distributed to 297 respondents which later was analyzed descriptively quantitatively using IBM SPSS Statistics 23. . Findings: The results shows that: 1) all question items can be used to measure the success rate of online learning and the calculation of the reliability of the question items obtained a score of 0.969 with very high criteria; 2) learning models that are often used during the pandemic is online learning with 186 people (63.5%) and the combination of online and offline learning with 76 people (25.9%) carried out at home (96.2%) with good internet conditions (72.7%), relatively good community economy (48.5%), online learning is carried out by giving assignments in the form of questions (73.7%) and providing material interactively online (46.8%), providing interactive material through online media and assignments in the form of students’ worksheets (84.6%) and assignments from teachers (43%), social media that are often used are WhatsApp group/Google Hangout/Facebook/ Messenger (76.1%), and the main obstacle for students during online learning is difficulty understanding teacher explanations (60.1%) and internet networks (48.8%); 3) the average level of online learning implementation in MTs in Pekanbaru City is 68.27% with